A comparative study to evaluate the effects of probiotic curd on Streptococcus mutans, Bifidobacterium dentium, and pH of saliva in caries-free children: An in vivo study - Nandhini B Selvarajan; Suresh Kumar Vasaviah; Ramesh Krishnan (Wolters Kluwer Medknow Publications, 2020)
Background: Dental caries is one of the commonest oral diseases that require early stages of prevention and intervention. The primary organisms related to dental caries are streptococcus mutans and lactobacilli. In the past decades, some of the non-pathogenic bacteria called probiotics have been added to the food products for the beneficial effect of human health. Intake of probiotic food products has been shown to have beneficial effects on the oral tissues. Hence the present study aimed to compare the levels of salivary pH, S. mutans, B. dentium counts in children consuming probiotic and non-probiotic curd. Methods and Material: 40 healthy caries free children were randomly allocated into two groups. First baseline salivary samples were collected from all the participants and tested for salivary pH, salivary B. dentium and S. mutans count. After collecting the baseline values test group of children were provided with probiotic curd whereas the control group were provided with non probiotic curd for 15 days. After 15 days of consumption of these dairy products, salivary samples were collected again and tested for salivary pH, salivary B. dentium and S. mutans count. Results: Probiotic curd was found to be more effective in reducing the colony counts of B.dentium and S.mutans .There was a marginal decrease in pH in both the groups but was well above the critical pH. Conclusions: Probiotic curd showed considerable level of decrease in colony counts of B.dentium, S.mutans and salivary pH when compared to normal curd.